Contextualizing systems biology : presuppositions and implications of a new approach in biology /: presuppositions and implications of a new approach in biology. (2015) - Döring, Martin, 1966-; Petersen, Imme, 1971-; Brüninghaus, Anne; Kollek, Regine, 1950-
No abstract available